2022
DOI: 10.1097/j.jcrs.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

Three-year clinical outcomes and posterior corneal elevation change after small-incision lenticule extraction in suspicious corneas

Abstract: This long-term study found that the safety and efficacy outcomes and posterior corneal elevation changes after SMILE is similar in eyes with suspicious tomographic features to that in normal eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…(21) In eyes with suspicious tomographic features that underwent SMILE, the 3-year change in PCE was − 1.22, indicating no forward displacemen. (22) Interestingly, in another study comparing posterior corneal elevation changes in eyes 10 years after laser in situ keratomileusis (LASIK) to unoperated normal eyes, the results revealed that points in the central 2 mm zone showed backward displacement after LASIK while increasing change in normal eyes. (23) Investigators have attributed this to hyperopic shift after corneal laser surgery: removal of central corneal tissue in corneal refractive surgery leads to relaxation of the peripheral corneal lamella, resulting in redistribution of corneal biomechanical balance.…”
Section: Discussionmentioning
confidence: 99%
“…(21) In eyes with suspicious tomographic features that underwent SMILE, the 3-year change in PCE was − 1.22, indicating no forward displacemen. (22) Interestingly, in another study comparing posterior corneal elevation changes in eyes 10 years after laser in situ keratomileusis (LASIK) to unoperated normal eyes, the results revealed that points in the central 2 mm zone showed backward displacement after LASIK while increasing change in normal eyes. (23) Investigators have attributed this to hyperopic shift after corneal laser surgery: removal of central corneal tissue in corneal refractive surgery leads to relaxation of the peripheral corneal lamella, resulting in redistribution of corneal biomechanical balance.…”
Section: Discussionmentioning
confidence: 99%